2019
DOI: 10.33751/jpsik.v3i2.1296
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KAMPANYE KOMUNIKASI PADA GERAKAN “BOGOH KA BOGOR” TERHADAP PERUBAHAN SIKAP MASYARAKAT (Studi Kasus KECAMATAN BOGOR TENGAH)

Abstract: This study uses a quantitative method entitled The effect of the communication campaign on the "BOGOH KA BOGOR" movement towards changes in people's attitudes. This study discusses how much influence the "Bogoh Ka Bogor" campaign has on the attitudes of the people of Bogor City. In this study, the independent variable is the communication campaign while the dependent variable is the change in community attitudes. The population is 104120 people, with a sample of 100 people. The sampling technique used is strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, there is another study that highlighted the effect of the "Bogoh Ka Bogor" (Love to Bogor) campaign on the attitude of the people of Bogor City. The study indicated that the communication campaign has a positive effect on people's attitudes, so if the communication campaign is improved then the attitude of the community will increase (Wulandari et al, 2019). From the perspective of campaign through advertisement as published on the article of Impact the #KasihLebihan Advertising Campaign Carried out by Gojek Indonesia Had on Public Perception, the outcome also said that there was a strong relationship between the impact of the #KasihLebihab advertising campaign on public perceptions.…”
Section: Modelmentioning
confidence: 94%
“…Moreover, there is another study that highlighted the effect of the "Bogoh Ka Bogor" (Love to Bogor) campaign on the attitude of the people of Bogor City. The study indicated that the communication campaign has a positive effect on people's attitudes, so if the communication campaign is improved then the attitude of the community will increase (Wulandari et al, 2019). From the perspective of campaign through advertisement as published on the article of Impact the #KasihLebihan Advertising Campaign Carried out by Gojek Indonesia Had on Public Perception, the outcome also said that there was a strong relationship between the impact of the #KasihLebihab advertising campaign on public perceptions.…”
Section: Modelmentioning
confidence: 94%